Effects of Low-Intensity Laser Irradiation on Wound Healing in Diabetic Rats - Hui Ma; Ying-xin Li; Hong-li Chen; Mei-ling Kang; Timon Cheng-Yi Liu (International Journal of Photoenergy)
Objective. The effects of low-intensity 630 nm semiconductor laser irradiation at 3.6 J/cm2 (LISL) on wound healing in diabetic rats were studied in this paper. Methods. 36 diabetic rats with dorsal cutaneous excisional wounds were divided into three LISL groups and a control group randomly. The three LISL groups were irradiated with LISL at 5, 10, and 20 mW/cm2 five times a week for two weeks, respectively. The process of wound healing was assessed by assessing blood glucose, calculating percentage of wound closure, histopathological evaluation, and immunohistochemical quantification. Results. Blood glucose of all groups remained at similar levels throughout the experiment. LISL could obviously promote wound contraction, fibroblasts proliferation, and collagen synthesis, alter bFGF and TGF-β1 expression, and reduce inflammatory reaction in the early and middle phases of chronic wound-healing process. However, LISL could not shorten cicatrization time, and the treatment effects were not sensitive to illuminate parameters in the later phase of the experiment. Conclusions. LISL might have auxiliary effects in the early and middle phases of wound healing in STZ-induced diabetic rats, but the reciprocity rule might not hold. The wound-healing process of early-phase diabetes rats shows typical characteristics of self-limited disease.